Chemical recycling of plastic waste for sustainable material management: A prospective review on catalysts and processes. (February 2022) - Huang, Jijiang; Veksha, Andrei; Chan, Wei Ping; Giannis, Apostolos; Lisak, Grzegorz
Abstract: Plastic waste management becomes imperative to prevent detrimental plastic-related environmental impacts. These relate to the huge plastic waste amount in both generation and disposal, non-biodegradability of most plastic waste, persistent nature of plastic waste in the environment, and the increasing concern of micro- and nanoplastics on human health. To continue exporting the use and benefits of plastic materials while mitigating their impacts to the planet, reuse, recovery and recycling of plastic waste are strongly encouraged. This would promote optimization of the value chain of plastic-based materials and validate the concept of a circular polymer economy. Chemical recycling techniques have been extensively studied for energy and material recovery from plastic waste, which are assisted by catalysts for enhanced process efficiency. In this review, the research progress of the applied catalysts in various thermochemical techniques is comprehensively summarized and assessed, covering the non-catalytic and catalytic pyrolysis, reforming of pyrolysis volatiles, and gasification processes. The impacts of feedstock, process conditions and catalyst properties on the quality and yield of the products are carefully examined. Finally, the practical challenges and perspectives on catalyst design and process improvement for material circularity are suggested and the emerging novel processes for the degradation of plastic waste are highlighted. Highlights: Applied catalysts for thermochemical recycling of plastic waste are analyzed. Impacts of feedstock, process conditions and catalyst properties are discussed. Practical challenges and perspectives on the catalyst design are suggested. Emerging green processes for the degradation of plastic waste are highlighted.